2020
DOI: 10.1002/jcop.22335
|View full text |Cite
|
Sign up to set email alerts
|

Taking another look at the sense of community index: Six confirmatory factor analyses

Abstract: Previous studies focusing on the effects of the social aspects of community have often used the Sense of Community Index (SCI), despite other research showing that it is not a good‐fit measure for its expected dimensions. Using a sample of students from Brigham Young University, we performed confirmatory factor analysis of the SCI to assess 1‐factor, 4‐factor, 1‐factor revised, 3‐factor revised, 1‐factor revised, 4‐factor revised, and 1‐factor revised models. Our study resulted in mixed findings: models were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…These items are drawn from the scale proposed by McMillan and Chavis (1986) and have been used by a number of researchers (e.g., Mak et al, 2009;Stevens et al, 2011). Ancillary analysis revealed that the unidimensional index best fit our data compared to multidimensional versions of the SCI, as the unidimensional index had the highest alpha score (α = .7652) and insofar as the construct validity of the multidimensional versions of the SCI are contested (e.g., Cope et al, 2020;Flaherty et al, 2014;Lounsbury & DeNeui, 1996;Obst & White, 2004). We made minor modifications to the original SCI questions in order to fit our study setting; specifically, we asked about a respondent's "university" rather than "community."…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…These items are drawn from the scale proposed by McMillan and Chavis (1986) and have been used by a number of researchers (e.g., Mak et al, 2009;Stevens et al, 2011). Ancillary analysis revealed that the unidimensional index best fit our data compared to multidimensional versions of the SCI, as the unidimensional index had the highest alpha score (α = .7652) and insofar as the construct validity of the multidimensional versions of the SCI are contested (e.g., Cope et al, 2020;Flaherty et al, 2014;Lounsbury & DeNeui, 1996;Obst & White, 2004). We made minor modifications to the original SCI questions in order to fit our study setting; specifically, we asked about a respondent's "university" rather than "community."…”
Section: Methodsmentioning
confidence: 86%
“…The SOC framework has been widely used, tested, and debated within community psychology (e.g., Cope et al, 2020;Glynn, 1981;Hill, 1996;Long & Perkins, 2003;McMillan & Chavis, 1986;Obst & White, 2004;Perkins et al, 1990;Peterson et al, 2008). For example, studies have shown that SOC is associated with such outcomes as community and individual health, group participation levels, well-being, empowerment, academic success, feelings of belonging, social cohesion in communities, and civic engagement (Chipuer & Pretty, 1999;Cicognani et al, 2008;Jacobs & Archie, 2008;Procentese, De Carlo et al, 2019;Talò et al, 2014;Townley et al, 2013).…”
Section: Sense Of Community On Campusmentioning
confidence: 99%
“…For each item, respondents were asked on a 5-point scale what effect that driver has on health and well-being, with 1 representing “no effect” and 5 representing a “very strong effect.” We dichotomized each item by grouping responses of 4 and 5 into one category representing respondents believing the driver to have a strong effect and responses of 1–3 into a category representing respondents not believing the driver to have a strong effect. An additional set of four items asked respondents about their beliefs about their community’s ability to drive health, which were adapted from the Sense of Community Index (SCI) [ 29 , 30 ]. We dichotomized each item by grouping responses “mostly” and “completely” into one category representing respondents believing their community does have the ability to drive health and responses “somewhat” and “not at all” into a category representing respondents not believing their community has the ability to drive health.…”
Section: Methodsmentioning
confidence: 99%
“…We dichotomized each item by grouping responses of 4 and 5 into one category representing respondents believing the driver to have a strong effect and responses of 1-3 into a category representing respondents not believing the driver to have a strong effect. An additional set of four items asked respondents about their beliefs about their community's ability to drive health, which were adapted from the Sense of Community Index (SCI) (29,30). We dichotomized each item by grouping responses "mostly" and "completely" into one category representing respondents believing their community does have the ability to drive health and responses "somewhat" and "not at all" into a category representing respondents not believing their community has the ability to drive health.…”
Section: Methodsmentioning
confidence: 99%